M-L band x-rays (3–3.5 KeV) from palladium coated targets for isochoric radiative heating of thin foil samples. (25th September 2015) - Kettle, B; Dzelzainis, T; White, S; Li, L; Rigby, A; Spindloe, C; Notley, M; Heathcote, R; Lewis, C L S; Riley, D
Abstract: We describe experiments designed to produce a bright M-L band x-ray source in the 3–3.5 keV region. Palladium targets irradiated with a 10 15 W cm −2 laser pulse have previously been shown to convert up to ∼2% of the laser energy into M-L band x-rays with similar pulse duration to that of the incident laser. This x-ray emission is further characterized here, including pulse duration and source size measurements, and a higher conversion efficiency than previously achieved is demonstrated (∼4%) using more energetic and longer duration laser pulses (200 ps). The emission near the aluminium K-edge (1.465–1.550 keV) is also reported for similar conditions, along with the successful suppression of such lower band x-rays using a CH coating on the rear side of the target. The possibility of using the source to radiatively heat a thin aluminium foil sample to uniform warm dense matter conditions is discussed.